?MIXED LIGAND COMPLEXES OF BIVALENT METAL IONS WITH 4,6-DIAMINO 2-HYDROXYPYRIMIDINE - Reddy, Maddy Satyanarayan; Reddy, K Siddiram; Goud, B Bharatb Kumar (Biological Sciences - PJSIR, 1998)
The interaction of Mn(II), Co(1I), Ni(II), Cu(II) and Zn(II) ions with 4,6-diamino 2-hydroxy pyrimidine in presence of biologically important Iigands like oxalic acid, malonic acid, o-amino phenol, o-phenylenediamine, 2,2'-bipyridyl, 1,10-phenanthroline and ethylenediamine has been investigated by potentiometric studies. The proton dissociation constant of the substituted pyrimidine, stability constant of the binary complexes of I: I and ternary complexes of I: 1:I molar ratios of the metal ion to ligands have been reported at 35°C and 0.1 M (KNO)) ionic strength.